FAKTOR DETERMINAN YANG MEMPENGARUHI KEJADIAN STUNTING PADA BALITA DI DESA OELNASI KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Mamoh, Kamilus; Seran, Agustina Abuk; Boimau, Serlyansie V.; Usnawati, Nana; Nurhanifah, Astin; Namangdjabar, Odi L.; Huru, Matje Meriaty; Boimau, Adriana M. (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Complementary stunting is a failure to grow that occurs from the beginning of life to the age of 2 years (the first 1000 days of life) caused by a lack of nutritious food intake that is not in accordance with nutritional needs in a long time bracket and the existence of recurrent infections. The impact of stunting is that the child's intelligence level is not optimal, the risk of decreasing productivity and suffering from diseases in adulthood. Research Objectives To analyze the relationship between determinants and stunting incidence in toddlers in Oelnasi Village, Central Kupang District, Kupang Regency. This study uses a type of analytical survey research with a cross-sectional approach. The research was carried out in July 2024 in Oelnasi Village, Central Kupang District, Kupang Regency. The population is mothers of toddlers who came to visit the posyandu as many as 60 respondents. Sampling uses the total population. The independent variable is the determinant factor while the dependent variable is the incidence of stunting in toddlers. Data collection uses questionnaires. The analysis uses descriptive analysis using frequency distribution while inferential analysis uses Chi-Square analysis. The results showed that there was a relationship between perception (p-0.000), behavior (p-0.000) and socio-culture (p-0.001) with stunting incidence. Conclusion: there is a relationship between perception, behavior and socio-culture with the incidence of stunting. Suggestion: It is important to always provide education and counseling to mothers of toddlers about stunting so that it provides a good understanding.